Harmony of Nature and Culture: The Case of Sirombu Beach and Aekhula Tradition in West Nias, North Sumatera Province - Sabam Syahputra Manurung; Furqan (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Tourism attraction cannot be established alone, it must be juxtaposed by all the potential around it. The phenomenon of research on the dual attractiveness of tourism activities in a destination has become popular because it provides its own challenges and happiness for researchers who are competent in this field. This research explores the harmonization between the natural beauty of Sirombu Beach and the rich cultural tradition of Aekhula in West Nias Regency, North Sumatra. Sirombu Beach, with its stunning beaches, attractive spots for surfing, continuously improved infrastructure, and stunning natural panorama, has become one of the leading marine tourism destinations in the region. On the other hand, Aekhula's traditions, which include distinctive dances, cultural values, and regional identity, are a rich cultural heritage that attracts tourists. This combination of natural beauty and cultural strength is likened to a harmonious relationship between lovers, which ultimately led to West Nias being known as the “Earth of Aekhula.” By applying the case study method, this research reveals how the synergy between natural and cultural attractions in West Nias provides a special attraction for tourists to come and enjoy various tourist and cultural attractions. The results of this study are expected to contribute to the development of sustainable tourism in the region by utilizing the existing natural and cultural potential in a balanced manner.